More than one, in more ways than one: multiple facial squamous cell Carcinoma with underlying psoriasis and reconstruction options - Ho Hui Lian; Chai Siew Cheng; Normala Basiron (ResearchGate, 2021)
Background: Reconstruction of multiple facial lesions detected simultaneously pose more difficulties. Taking into the account on the importance of facial aesthetic subunits and possible requirement of future reconstructions, available options should be explored carefully. Case presentation: This report presents a case of multiple facial skin squamous cell carcinoma in a patient with lower eyelid ectropion from previous cheek advancement flap and underlying psoriasis. Lower eyelid was reconstructed with bipedicled Tripier flap from the upper lid. An analysis of the surgical options, reconstructions and the results observed during follow-up were discussed. Conclusion: Achieving surgical clearance with minimal tissue defect is the main goal in any oncologic resection. Skin laxity and local tissue quality should be considered in all reconstructions. In lower eyelid reconstruction, establish horizontal rather than vertical tension